ACADEMIC PROCRASTINATION OF STUDENTS - Dyla Fajhriani N (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The process of college education differs from educational institutions in secondary schools or primary schools because the subject matter given to students is broader than the subject matter provided at secondary schools or elementary schools. students must also learn to prepare themselves not only to do their work but also in facing exams. Students often procrastinate on assignments given by lecturers for a period of a week. Most students will do their work when the allotted time is getting closer. The actual tasks can be completed faster than the deadline it is not done immediately because they feel that if done faster or with the Overnight Speeding System